The Effect of Transesophageal Echocardiography Probe Insertion in Endotracheal Tube Cuff Pressure in Adult Cardiac Surgical Patients. - Parajuli, Santosh Sharma; Gyawali, Parbesh Kumar; KC, Suraj (Nepalese Heart Journal, 2021)
Background and Aims: Insertion of transesophageal echocardiography probe in cardiac surgical patient is a routine practice for surgical planning and decision making. However it may increase the endotracheal tube cuff pressure as it lies adjacent to the posterior wall of trachea. The aim of this study is to evaluate the changes in cuff pressure after insertion of the transesophageal echocardiography probe and after completion of initial manipulation of the transesophageal echocardiography probe during various examinations in adult cardiac surgical patients. Methods: Thirty six patients undergoing elective cardiac surgery requiring Transesophageal Echocardiography (TEE) monitoring were enrolled in the study. After induction of general anesthesia and endotracheal intubation cuff pressure were measured at 3 points of time; just after intubation (T1), after transesophageal probe insertion (T2) and after initial completion of TEE study (T3). The mean increase in cuff pressure at various point of time were compared. Results: The cuff pressure (mean±SD) at T1, T2 and T3 were 24.61±2.72, 30.22±5.61 and 32.25±4.45 cm of H2O respectively.The cuff pressure increased significantly from T1 to T2 (p<0.001) and from T1 to T3 (p<0.001). The cuff pressure was > 30 cm of H2O in 18 (50%) of patients at T3 which was readjusted back to 25-30 cm of H2O by with drawing air from the cuff. Conclusion: Endotracheal tube cuff pressure should be routinely monitored either intermittently or continuously after transesophageal echocardiography probe insertion till it is in situ and pressure should be readjusted to avoid unwanted complications.